BASED EDUCATIONAL MANAGEMENT ISLAMIC AESTHETHICS - Arifin, Zuhairansyah; Andriani, Tuti; Faruq, Umar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic aesthetics-based education management is an approach to education management that is oriented towards Islamic aesthetic values. The Islamic aesthetic values referred to include beauty, harmony, balance and harmony. This approach emphasizes the importance of creating an educational environment that is beautiful, harmonious and comfortable for all parties involved in the educational process. Islamic aesthetics-based education management has several advantages, including: Can improve the quality of education, because a beautiful and comfortable educational environment can motivate students to study harder.Can create an atmosphere that is conducive to the teaching and learning process, because students will be more comfortable and at home studying in a beautiful and comfortable environment. Can form positive student characters, because a beautiful and comfortable educational environment can foster a sense of love and beauty in students.This approach can be applied at all levels of education, from early childhood education to higher education. Implementation can be done in various ways, including:Creating beautiful and comfortable building designs and educational facilities.Create a clean, neat and wellorganized learning environment.Creating a conducive learning atmosphere by implementing good classroom management.Using interesting and innovative learning media. Organizing aesthetic activities, such as art, music and drama. Education management based on Islamic aesthetics is one approach that can be used to improve the quality of education in Indonesia. This approach can have a positive impact on students, educators and the educational environment